Doped biochar from an invasive plant "Eichhornia crassipes" for the oxygen reduction reaction. (15th August 2022) - Morales Salas, L.; Salazar, M. Ruiz; Escobar, B.
Abstract: N-doped carbon derived from Eichhornia crassipes biomass is appealing since it transforms a weed into a sustainable resource for Fuel Cell applications. Activated carbons were prepared using KOH at 700 °C with N2; before being doped with hydrazine. As a result of the activation process, the samples EC-SAP (not doped) and EC-SAPD got a surface area (SBET ) of 1577 and 1222 m 2 g −1, respectively. Besides, both samples showed the carbonaceous D and G bands indicative. The presence of carbon in EC-SAP and 3.56% of N in EC-SAPD was corroborated by elemental analysis CHNS. The testing system for the Oxygen Reduction Reaction activity consisted of a three-electrode cell with 0.5 M KOH. The EC-SAPD sample showed promising performance for ORR with a high cathodic reaction potential of 0.82 V and a transfer of 3.6 electrons. Its surface area and nitrogen concentration improve its performance compared to EC-SAP. Highlights: Activated and doped activated biochars were prepared by biomass from " Eichhornia crassipes. ". EC-SAP and EC-SAPD were evaluated for ORR in an alkaline medium. The activity toward ORR was favored by high surface area and nitrogen content.